Modifikasi Atmosfir Dalam Pengemasan Untuk Daging Segar - Triyanto Hadisoemarto (Balai Besar Kimia dan Kemasan, 2001)
Modified Atmosphere Packaging (MAP) is the enclosure of meat in high gas barrier materials, in which the gaseous environment has been changed especially to maintain the colour of meat and reduce microbiological growth - with the intent of extending shelf life.MAP which has been applied commercially to fresh meat may be devided into two basic techniques, high oxygen MAP and low oxygen MAP. The shelf life and safety of fresh meat in this packaging method is influenced by a number of factors, namely the nature of meat, the gaseous environment inside the package, the nature of the package, the storage temperature, and the packaging process and machinery.